Detecting Mild Cognitive Deficits in Parkinson's Disease: Comparison of Neuropsychological Tests. Issue 11 (14th September 2018) - Hoogland, Jeroen; van Wanrooij, Lennard L.; Boel, Judith A.; Goldman, Jennifer G.; Stebbins, Glenn T.; Dalrymple‐Alford, John C.; Marras, Connie; Adler, Charles H.; Junque, Carme; Pedersen, Kenn F.; Mollenhauer, Brit; Zabetian, Cyrus P.; et al.
Abstract: Background: Numerous neuropsychological tests and test versions are used in Parkinson's disease research, but their relative capacity to detect mild cognitive deficits and their comparability across studies are unknown. The objective of this study was to identify neuropsychological tests that consistently detect cognitive decline in PD across studies. Methods: Data from 30 normed neuropsychological tests across 20 international studies in up to 2908 nondemented PD patients were analyzed. A subset of 17 tests was administered to up to 1247 healthy controls. A 2‐step meta‐analytic approach using standardized scores compared performance in PD with normative data. Results: Pooled estimates of the differences between PD and site‐specific healthy controls identified significant cognitive deficits in PD patients on 14 test scores across 5 commonly assessed cognitive domains (attention or working memory, executive, language, memory, and visuospatial abilities), but healthy control performance was statistically above average on 7 of these tests. Analyses based on published norms only, as opposed to direct assessment of healthy controls, showed high between‐study variability that could not be accounted for and led to inconclusive results. Conclusions: Normed neuropsychological tests across multiple cognitive domains consistently detect cognitive deficits in PD when compared with site‐specific healthy control performance, but relative PD performance was significantly affected by the inclusion and type of healthy controls versus the use of published norms only. Additional research is needed to identify a cognitive battery that can be administered in multisite international studies and that is sensitive to cognitive decline, responsive to therapeutic interventions, and superior to individual cognitive tests. © 2018 International Parkinson and Movement Disorder Society